A window into the emergence of agile software development landscape in Indonesia - Salleh, Norsaremah; Al-Kautsar, Emyr; Hoda, Rashina; Asnawi, Ani Liza (SCRG Publication, 2014)
Since the introduction of the Agile Manifesto over a decade ago, software industries around the world have started to change their software development process from traditional to Agile methods. A number of research studies conducted in Asia Pacific countries such as Malaysia, India, and New Zealand have provided valuable insight into Agile adoption and practice in these countries. However, very little is known about the state of Agile adoption in Indonesia. This study aims to investigate the adoption of Agile methods among 21 software practitioners in Indonesia using survey method. This includes the perceptions and level of awareness in using Agile methods as well as the challenges in adopting these methods. We found that major challenges revolved around the people, organizational and customer related issues. Findings from this study can be used as evidence about Agile adoption and practice in Indonesia and as a roadmap for future Agile-focused research studies.